Application of SiO2 nanoparticles as pretreatment alleviates the impact of drought on the physiological performance of Prunus mahaleb (Rosaceae) - Peyman Ashkavand; Mehrdad Zarafshar; Masoud Tabari; Javad Mirzaie; Amirreza Nikpour; Seyed Kazem Bordbar; Daniel Struve; Gustavo Gabriel Striker (Boletín de la Sociedad Argentina de Botánica, 2018)
We studied the physiological responses of Prunus mahaleb (Mahaleb) seedlings to drought stress when previously irrigated (or not) with different concentrations of SiO2 nanoparticles (SNPs). SNPs were applied at four concentrations (0, 10, 50 and 100 mg L-1) for 45 days, and then seedlings were subjected to three watering treatments including low (300 mL water every 3 d), moderate (150 mL water every 3 d) and severe drought stress (no irrigation) for 19 days. Results showed that gas exchange – photosynthesis, stomatal conductance, and transpiration rate – were significantly less impacted by severe drought stress when seedlings were pretreated with SNPs at high concentrations. Beneficial effects of SNPs pretreatment were evident in the nutritional status of the plants as the concentration of N, P and K, were maintained at similar levels than in well-watered seedlings. Pretreated seedlings were able to maintain the root length and to reduce the impact of severe drought on root dry mass accumulation. Therefore, application of SNPs as pretreatment should be considered as a promising agronomic practice in sites prone to suffer from water deficit.